THE ROLE OF STEREOTACTIC ABLATIVE RADIOTHERAPY IN THE TREATMENT OF OLIGOMETASTATIC DISEASE – A CLINICAL REVIEW - Augustyniak, Kinga; Szweda, Franciszek; Poczwardowski, Tomasz; Kaczmarek, Adrianna; Kowalska, Katarzyna Anna; Latos, Jakub Tomasz; Chwalczuk, Marcin; Grygorcewicz, Olivia; Koneczna, Marta; Krystyniak, Karolina Alicja (International Journal of Innovative Technologies in Social Science, 2026)
Oligometastatic disease (OMD) is defined as an intermediate stage between localised cancer and widespread metastasis. The objective of this paper is to critically evaluate the clinical efficacy and safety of stereotactic ablative body radiation (SABR) in the treatment of OMD.This evaluation is based on a review of randomised trials from 2012 to 2025. A comprehensive analysis of pivotal clinical trials has revealed that the utilisation of ablation therapy is associated with a substantial enhancement in progression-free survival and overall survival, particularly in carefully selected patient populations. This assertion is corroborated by empirical evidence from studies conducted on prostate cancer (STOMP, ORIOLE) and specific subgroups of lung cancer (SINDAS). However, a discrepancy in outcomes was observed between patients receiving modern immunotherapy (NRG-LU002) and those treated for breast cancer (NRG-BR002), indicating a significant correlation between the efficacy of SABR and tumour biology, as well as the systemic treatment regimen employed.A thorough analysis of the existing evidence was conducted, encompassing the limitations arising from population heterogeneity, inadequate sample sizes in clinical trials, and the paucity of large-scale phase III trials for numerous histopathological types. The review also underscores the pivotal function of meticulous patient selection based on biomarkers, including circulating tumour DNA.The clinical findings suggest that SABR is a safe and highly effective method that allows for the deferral of toxic systemic treatment in selected patients. However, definitive standards for all subgroups will be established by ongoing phase III trials.